2023
DOI: 10.3389/fphar.2023.1275000
|View full text |Cite
|
Sign up to set email alerts
|

Natural compounds as lactate dehydrogenase inhibitors: potential therapeutics for lactate dehydrogenase inhibitors-related diseases

Jung Ho Han,
Eun-Ji Lee,
Wonyoung Park
et al.

Abstract: Lactate dehydrogenase (LDH) is a crucial enzyme involved in energy metabolism and present in various cells throughout the body. Its diverse physiological functions encompass glycolysis, and its abnormal activity is associated with numerous diseases. Targeting LDH has emerged as a vital approach in drug discovery, leading to the identification of LDH inhibitors among natural compounds, such as polyphenols, alkaloids, and terpenoids. These compounds demonstrate therapeutic potential against LDH-related diseases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 353 publications
0
3
0
Order By: Relevance
“…Both enzymes have important metabolic roles. LDH is an enzyme of anaerobic metabolism, while MDH catalyzes one of the Krebs cycle reactions and can be considered an aerobic metabolism enzyme [38,39]. The results of our study showed a statistically significant increase in the total activities of LDH and MDH in the HPA group compared to the active control group (CPA), indicating an effect of HHcy on the total activity of these enzymes.…”
Section: Discussionmentioning
confidence: 49%
“…Both enzymes have important metabolic roles. LDH is an enzyme of anaerobic metabolism, while MDH catalyzes one of the Krebs cycle reactions and can be considered an aerobic metabolism enzyme [38,39]. The results of our study showed a statistically significant increase in the total activities of LDH and MDH in the HPA group compared to the active control group (CPA), indicating an effect of HHcy on the total activity of these enzymes.…”
Section: Discussionmentioning
confidence: 49%
“…Pyruvate regulation is complex and involves key enzymes, particularly PDK and LDHA. PDK governs the entry of pyruvate into the citric acid cycle and glycolysis [96], whereas LDHA catalyzes the conversion of pyruvate to lactate under anaerobic conditions [97]. Notably, PDK and LDHA are significantly associated with EGFR-TKI resistance.…”
Section: Enhanced Glycolysis In Egfr-tki-resistant Nsclcmentioning
confidence: 99%
“…Notably, key findings from current research underscore the promising role of natural products in mitigating OA symptoms, potentially influencing macrophage behavior and inflammatory responses within the joint microenvironment (7,8). Crucially, alkaloids, widespread in nature (9), play a key role in Traditional Chinese Medicine's therapeutic effects, exhibiting significant anti-cancer, anti-inflammatory, and antioxidant activities (10)(11)(12). In this context, Aconitum, commonly known as "wutou," stands out as a repository of approximately 450 alkaloids and has been extensively utilized for treating various diseases in China, Japan, and other regions (13, 14).…”
Section: Introductionmentioning
confidence: 99%